Absolute Hyperglycemia versus Stress Hyperglycemia Ratio for the Prognosis of Hospitalized Patients with COVID-19 in the First Months of the Pandemic: A Retrospective Study - Matias, AA (2022)
Diabetes is a risk factor for greater severity of coronavirus disease 2019 (COVID-19). The stress hyperglycemia ratio (SHR) is an independent predictor of critical illness, and it is reported to have a stronger association than absolute hyperglycemia. The aim of this study was to assess the relationship of absolute hyperglycemia and SHR with the severity of COVID-19, since there are no studies investigating SHR in patients with COVID-19. We conducted a retrospective observational study on hospitalized patients with COVID-19 in the first months of the pandemic, regarding absolute hyperglycemia, SHR, and severity outcomes. Of the 374 patients, 28.1% had a previous diagnosis of type 2 diabetes. Absolute hyperglycemia (64.8% versus 22.7%; p < 0.01) and SHR [1.1 (IQR 0.9-1.3) versus 1.0 (IQR 0.9-1.2); p < 0.001] showed a statistically significant association with previous diabetes. Absolute hyperglycemia showed a significant association with clinical severity of COVID-19 (79.0% versus 62.7%; p < 0.001), need for oxygen therapy (74.8% versus 54.4%; p < 0.001), invasive mechanical ventilation (28.6% versus 11.6%; p < 0.001), and intensive care unit (30.3% versus 14.9%; p = 0.002), but not with mortality; by contrast, there was no statistically significant association between SHR and all these parameters. Our results are in agreement with the literature regarding the impact of absolute hyperglycemia on COVID-19 severity outcomes, while SHR was not a significant marker. We therefore suggest that SHR should not be evaluated in all patients admitted in the hospital for COVID-19, and we encourage the standard measures at admission of blood glucose and HbA1c levels.